Analisis Kemampuan Lahan di Kota Padang Berbasis Sistem Informasi Geografis - Dwi Marsiska Driptufany; Ramadhan, Bagus Arie; Ilham Armi; Dwi Arini; Defwaldi Defwaldi (Jurnal Sains dan Ilmu Terapan, 2025)
Land capability encompasses soil characteristics, topography, drainage, and environmental factors that support activities in a given area. Improper land use without conservation efforts can accelerate erosion and reduce productivity. Padang City is classified as a disaster-prone area due to its coastal location, low-lying land, high rainfall, and numerous rivers. Population growth increases the demand for built-up areas and water absorption land. This study analyzes land capability classifications in Padang City using a Geographic Information System (GIS) with a descriptive quantitative approach. The results indicate four land capability categories: very high, relatively high, moderate, and low. The majority of the area (45.88% or 31,843.30 ha) falls into the moderate category, allowing development with proper management. Areas with very high (22.79% or 15,816.54 ha) and relatively high (19.32% or 13,409.84 ha) capability are generally found in stable lowland areas, making them suitable for urban activities. Meanwhile, low-capability areas (12% or 8,328.52 ha) are located in steep hilly regions that require special management attention.